Effet d’une formation à l’entraide suivie d’une supervision continue sur la communication interpersonnelle et le développement personnel d’entraidants - Simard, Marie-Pierre; Ouellette, Jean-Guy (Canadian Journal of Counselling and Psychotherapy, 2011)
The following article summarizes a study conducted among a group of peer counsellors. The main objective was to verify if a peer counselling training and a continuous supervision program had an effect on learning interpersonal communication skills and personal development, comparatively to a control group having received no training or supervision. The data was collected among 34 university level students. The analysis of the results demonstrated that peer counsellor training and a continuous supervision program contributed significantly to the improvement of the peer counsellors interpersonal communication skills, while during this period there was no change with the control group on this variable. A continuous supervision program following a peer counselling training has significant effects on personal development of peer counsellors, but it has no effect on the control group.